Analysis of The Influence of Organizational Engagement and Digitalization in Work Environment on Loyalty of Generation Y Employees - Senoaji, Fauzie; Indajang, Kevin; Malini Lubis, Fatimah; Ariani, Dian; Hadi, Syamsul (SEULANGA SYSTEM PUBLISHER, 2024)
The purpose of this study is to examine how supportive work environments affect organizational engagement and how that affects employee retention. In this study, questionnaires and interviews were employed as data collection methods. Descriptive and causal research methodologies were used in this study. The research's target demographic comprises Generation Y workers with permanent job status in property companies. Non-probability sampling combined with judgmental sampling is the sampling method employed in this study. One hundred people made up the study's sample. Multivariate analysis is typically used with this data analysis method. The study's findings indicate no statistically significant correlation between a supportive work environment and employee retention. On the other hand, with a very low p-value, a supportive work environment significantly positively affects organizational engagement. In addition, it was discovered that staff retention is significantly positively impacted by organizational engagement. These findings highlight the value of fostering a positive work environment to raise organizational engagement among employees, which can increase retention rates.